Power loss and harmonic minimization at distribution system with electric vehicle by passive filter using modified lightning search algorithm - Syed Norazizul Syed Nasir, 1985-, author; Mohd. Wazir Mustafa, supervisor; Jasrul Jamani Jamian, 1985-, supervisor; Fakulti Kejuruteraan. Sekolah Kejuruteraan Elektrik (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2019)
Thesis (Ph.D (Kejuruteraan Elektrik)) - Universiti Teknologi Malaysia, 2019